Gestational trophoblastic neoplasia with primary lung cancer and mesenchymal tumor of sigmoid colon: a case report and literature review - HongYe Li; Meng Sun; Jing Jiang; Bin Shi; BaoHua Wang; Lei Wang; WenXin Wu; WenYan Wang (BMC, 2023)
Abstract Background Gestational trophoblastic neoplasia (GTN) is rare, and it is even rarer for GTN to merge with primary malignant tumors in other organs. Herein is described a rare clinical case of GTN combined with primary lung cancer and mesenchymal tumor of the sigmoid colon, followed with literature review. Case presentation The patient was hospitalized due to diagnosis of GTN with primary lung cancer. Firstly, two cycles of chemotherapy including 5-fluorouracil (5-FU) and actinomycin-D(Act-D) was given. Laparoscopic total hysterectomy and right salpingo-oophorectomy was performed during the third chemotherapy. During the operation, a 3*2 cm nodule was removed which was protruded from the serous surface of the sigmoid colon, and the nodule was confirmed mesenchymal tumor pathologically, in accord with gastrointestinal stromal tumor. During the treatment of GTN, Icotinib tablets were taken orally to control the progression of lung cancer. After 2 cycles of consolidation chemotherapy of GTN, she received thoracoscopic lower lobe of right lung lobectomy and the mediastinum lymph nodes removal. She undertook gastroscopy and colonoscopy and the tubular adenoma of the descending colon was removed. At present, the regular follow-up is taken and she remains free of tumors. Conclusions GTN combined with primary malignant tumors in other organs are extremely rare in clinical practice. When imaging examination reveals a mass in other organs, clinicians should be aware of the possibility of a second primary tumor. It will increase the difficulty of GTN staging and treatment. We emphasis the importance of the collaboration of multidisciplinary teams. Clinicians should choose a reasonable treatment plan according to the priorities of different tumors.